Planning Of School Heads In Implementing School-Based Management - Pulita, Henny Lesma; Fitria, Happy; Rohana (Jurnal Pendidikan Tambusai, 2021)
This study to determine the form of Principal Planning in Implementing School-Based Management at SMP Negeri 10 OKU. This study used a qualitative method. Data collection was carried out by interview, observation, documentation. From this research, it can be concluded that the form of the principal planning process in implementing SBM at SMP Negeri 10 OKU has been implemented well. This is evidenced by the implementation of deliberations by teachers, staff, committees in planning activity programs to be implemented, along with the necessary budget funds. The principal in implementing SBM at SMPN 10 OKU, is as follows: the principal tries to apply a democratic leadership pattern, to achieve this, the principal implements work discipline, togetherness, loyalty, high commitment in carrying out tasks.